A CROSS-SECTIONAL SURVEY-BASED INVESTIGATION ON KNOWLEDGE, ATTITUDE, AND PRACTICE OF PHARMACOVIGILANCE AMIDST HEALTHCARE PROVIDERS OF JORHAT CITY, ASSAM - DEY, NAYAN; AZIZ, SAHID; RIBA, NYAGI; JESUDASAN, RAJESH (International Journal of Pharmacy and Pharmaceutical Sciences, 2025)
Objective: Among the main causes of increasing rates of sickness, death rates, and medical cost expenses is an Adverse Drug Reaction (ADRs). To guarantee improved patient safety, the Pharmacovigilance Programme of India (PvPI) encourages every healthcare worker to report possible ADRs. However, current data indicates that suspected ADRs are not being reported enough. In light of this, the current study was carried out to gauge the healthcare provider’s Knowledge, Attitude, and Practice (KAP) on pharmacovigilance and to investigate the causes behind the underreporting of suspected ADRs in Jorhat City, Assam. Methods: KAP of HCPs, comprising pharmacists, physicians as well as nurses, about pharmacovigilance is the subject of this observational investigation with a cross-section, carried out at Jorhat City, Assam. The pretested and peer-reviewed multiple-choice test consisting of 30 queries was utilized to assess the knowledge (1-16), attitude (17-22), and practice (23-30) between 61 HCPs of the city and the responses were collected after 30 min from each HCP. Utilizing Microsoft Excel software, data were analyzed and expressed as a percentage. Results: 53 responses-21 pharmacists, 20 nurses, and 20 doctors were obtained from 61 surveys. Although the Healthcare Professionals demonstrated a good attitude (73.38%) and adequate knowledge, they did not perform pharmacovigilance for several reasons, the primary one being training on ADR reporting (34.33%), didn’t send any suspected ADR report to the manufacturer (44.17%), haven’t seen pharmacist reporting ADR (36.67%) and also due to not available of ADR Reporting form (25.11%). Conclusion: The HCPs exhibited a good attitude. Still, the modification from attitude to knowledge and practice wasn't sufficient. Expertise and training can be significantly raised by making ADR reporting forms more accessible and adopting accessible techniques like instruction and guidance on reporting adverse drug reactions.